IMPROVING MATHEMATICAL LEARNING OUTCOMES USING ORIGINAL TEACHING AIDS AT 5TH GRADE STUDENTS IN SDN 189/V KUALA INDAH, WEST TANJUNG JABUNG DISTRICT LESSON YEAR OF 2018/2019 - Sumarlan Sumarlan; Masda Masda (Department of Primary education, Faculty of Teacher Training and Education, Universitas Su, 2019)
each cycle consisting of planning, action, observation, and reflection. The aspects that observed in each cycle are the student activities, and the learning process of fractions using the original teaching aids. The subjects of this research were 15 students consisting of 6 male students and 9 female students. The results of research of the students' abilities in the fractions subject, each cycle have an improvement. Cycle I, the average score of the students was 53.80 with a percentage of completeness is 13.33%, students who achieved KKM only 2 students. Cycle II, the average score of students was 67.53 with a percentage of completeness is 66.67%, students who achieved KKM are 10 students. Cycle III, the average score of students was 77.33 with a percentage of completeness is 86.67%, students who achieved KKM are 13 students. From applying the three cycles, there was an improvement in students' abilities on the fractions subject. The increases of the average score from cycle I to cycle II is 13.73, the percentage increase to 53.33%, and the students who reach KKM increase to 8 students. The increase in the average score from cycle II to cycle III is 9.80, the increase in the percentage is 20%, and the increase number of students who reach KKM is 3 students. Based on the indicators of successes in the cycle III, shows that the teaching aids from the original objects that are applied can improve the students' abilities in the fractions subject in 5th grade of SDN 18/V Kuala Indah, West Tanjung Jabung District. Keywords: Mathematics Learning Results, Original Teaching Aids